Faktor-faktor Yang Mempengaruhi Intensi Menabung Dengan Metode Importance Performance Matrix Analysis (IPMA) Pada Bank Sumut Syariah KCP Multatuli di Kota Medan - Perdana, Kanda Juwana; Irham, Mawaddah; Arif, Muhammad (Journal of Computer Science and Information System(JCoInS), 2024)
This study aims to identify the factors that play a role in influencing the intention to save in Islamic banks, including religiosity, service quality, and trust with the IPMA method. This research uses quantitative research methods. The population in this study were the customers of Bank Sumut Syariah Kcp Multatuli Medan totaling 6,382. Sampling was carried out using non-probability sampling and incidental sampling using the Slovin formula for 100 customers. Data collection techniques used a questionnaire which was measured by a Likert scale. The data analysis used was multiple linear regression analysis with the help of the SPSS program. The results showed that the religiosity variable had an effect on the intention to save. The significant value (sig) for the effect of X1 on Y was 0.049 <0.05 and the tcount value was 1.995, which was less than 1.984. Both service quality have a positive effect on the intention to save a significant value (sig) for the effect of X2 on Y is 0.756 > 0.05 and the tcount value is 0.312 smaller <1.984. The three beliefs have no effect on saving intentions. Simultaneously the variables of religiosity, service quality and trust have a significant effect on the intention to save. The IPMA method shows that religiosity and service quality are factors that have a high level of importance and high performance, while the trust variable has a low level of importance and low performance.